Saltcedar (Tamarix mascatensis) inhibits growth and spatial distribution of eshnan (Seidlitzia rosmarinus) by enrichment of soil salinity in a semi-arid desert - Erfanifard, Yousef; Khosravi, Elaheh (Plant and soil, 2019)
Background and aims Understanding the species associations in dryland sparse and patchy vegetation requires information on species intra- and interspecific interactions and their response to environmental heterogeneity. To better understand the coexistence mechanisms of saltcedar ( Tamarix mascatensis ) and eshnan ( Seidlitzia rosmarinus ) in central deserts of Iran, we analysed the spatial distributions and soil chemical properties of their mixed stands. Methods We applied uni- and bivariate point process statistics together with mark correlation functions and soil information under the species canopy and in the interspaces to evaluate plant-to-plant interactions. Results Tamarix and Seidlitzia were both highly aggregated in conspecific clusters, and the species were significantly segregated at small spatial scales. Interestingly, we found that the density of conspecific neighbours in Tamarix clusters was higher than Seidlitzia (approximately 9 times more), although the mean density of Tamarix (29.4 shrubs ha −1 ) was lower than Seidlitzia (357.3 shrubs ha −1 ). For both species, intraspecific interactions had negative effects on their size, which was more evident in Tamarix . Our results showed that the size of Seidlitzia was strongly and negatively depended on the proximity of nearby Tamarix . Additionally, the two species improved soil chemical properties and moisture under their canopy compared to bare soil; however, soil salinity under Tamarix (24.29 dS m −1 ) was higher than Seidlitzia (1.68 dS m −1 ). Conclusions According to the segregated spatial pattern of the species and negative effects of Tamarix neighbourhood on Seidlitzia growth, we suggest that high soil salinity beneath Tamarix canopy likely reduces interspecific interactions between the two species and affects Seidlitzia growth. Furthermore, our results indicate no spatial mixture of Tamarix and Seidlitzia , contrary to our expectations, although we still encourage further research on the co-occurrence of the species in the region.